Financial toxicity, mental health, and gynecologic cancer treatment: The effect of the COVID‐19 pandemic among low‐income women in New York City - Chen, Yiting Stefanie; Zhou, Zhen Ni; Glynn, Shannon M.; Frey, Melissa K.; Balogun, Onyinye D.; Kanis, Margaux; Holcomb, Kevin; Gorelick, Constantine; Thomas, Charlene; Christos, Paul J.; Chapman‐Davis, Eloise (Cancer, 2021)
BACKGROUND New York City (NYC) emerged as an epicenter of the COVID‐19 pandemic, and marginalized populations were affected at disproportionate rates. The authors sought to determine the impact of COVID‐19 on cancer treatment, anxiety, and financial distress among low‐income patients with gynecologic cancer during the peak of the NYC pandemic. METHODS Medicaid‐insured women who were receiving gynecologic oncology care at 2 affiliated centers were contacted by telephone interviews between March 15 and April 15, 2020. Demographics and clinical characteristics were obtained through self‐report and retrospective chart review. Financial toxicity, anxiety, and cancer worry were assessed using modified, validated surveys. RESULTS In total, 100 patients completed the telephone interview. The median age was 60 years (range, 19‐86 years), and 71% had an annual income <$40,000. A change in employment status and early stage cancer (stage I and II) were associated with an increase in financial distress (P < .001 and P = .008, respectively). Early stage cancer and telehealth participation were significantly associated with increased worry about future finances (P = .017 and P = .04, respectively). Lower annual income (<$40,000) was associated with increased cancer worry and anxiety compared with higher annual income (>$40,000; P = .036 and P = .017, respectively). When controlling for telehealth participation, income, primary language, and residence in a high COVID‐19 prevalence area, a delay in medical care resulted in a 4‐fold increased rate of anxiety (P = .023, 95% CI, 1.278‐14.50). Race was not significantly associated with increased financial distress, cancer worry, or anxiety. CONCLUSIONS Low socioeconomic status was the most common risk factor for increased financial distress, cancer worry, and anxiety. Interventions aimed at improving access to timely oncology care should be implemented during this ongoing pandemic. Low socioeconomic status is the most common risk factor for increased financial distress, cancer worry, and anxiety among patients with Medicaid who are receiving gynecologic oncologic care during the coronavirus disease 2019 (COVID‐19) pandemic. Interventions aimed to improving access to timely oncology care for this population should be implemented during this ongoing pandemic.